Dynamic web service selection group decision-making method based on hybrid QoS. (1st January 2013) - Zhang, Longchang; Yang, Yanhong
Open and dynamic internet environment, multi-period QoS and multiple QoS registry centres increased the difficulty of service selection. To solve difficulties above, a hybrid QoS model is introduced supporting real numbers, interval numbers, triangular fuzzy numbers and intuitionistic fuzzy numbers and multi-period hybrid QoS aggregating operator firstly. Furthermore, dynamic web service selection group decision-making method based on hybrid QoS (DWSSGDM_HQ) is presented to support proposed models of QoS, multiple QoS registry centres. DWSSGDM_HQ includes four main steps: converting hybrid QoS into intervals, calculating weighted normalised decision-matrix, determining the group positive-ideal and group negative-ideal solution, and calculating the close-degrees of candidates. Finally, some experiments are given using actual QoS data to demonstrate the benefits and effectiveness of our approach.